Pelatihan Pengenalan Komponen Instalasi Listrik Rumah Tangga dan Perhitungan KWH Meter - Linda sartika; Ismit mado; Abdul Muis Prasetia; Achmad Budiman; Abil Huda (CV. Multi Kreasi Media, 2022)
Electricity in people's life is an inseparable part. This can be seen through home electricity needs that reach all levels of society, ranging from people with low economic status to people with high economic status, so it can be said that electricity needs are a primary need. In general, the benefits of electricity for the community in the home include lighting, heating, machinery and others. But on the other hand, electricity is very dangerous for our safety if it is not managed properly. Most people have experienced or felt an electric shock, from those who only felt shocked to those who felt very miserable. Through an analysis of the situation and partner problems, we and the community agreed that there is a need for more understanding about the components of electrical installations and the calculation of KWH meters to reduce the risk of misuse. Based on the results that have been achieved in this community service program and its benefits for the general public. This training is able to provide basic introduction to home installations. This training provides basic introduction to equipment and components, test and measurement systems, and simple installation for homes.